Systematic study of tissue factor expression in solid tumors. Issue 2 (13th August 2022) - de Bono, Johann S.; Harris, Jeffrey R.; Burm, Saskia M.; Vanderstichele, Adriaan; Houtkamp, Mischa A.; Aarass, Saida; Riisnaes, Ruth; Figueiredo, Ines; Nava Rodrigues, Daniel; Christova, Rossitza; Olbrecht, Siel; Niessen, Hans W. M.; et al.
Abstract: Background: Elevated tissue factor (TF) expression, although restricted in normal tissue, has been reported in multiple solid cancers, and expression has been associated with poor prognosis. This manuscript compares TF expression across various solid tumor types via immunohistochemistry in a single study, which has not been performed previously. Aims: To increase insight in the prevalence and cellular localization of TF expression across solid cancer types, we performed a detailed and systematic analysis of TF expression in tumor tissue obtained from patients with ovarian, esophageal, bladder, cervical, endometrial, pancreatic, prostate, colon, breast, non‐small cell lung cancer (NSCLC), head and neck squamous cell carcinoma (HNSCC), and glioblastoma. The spatial and temporal variation of TF expression was analyzed over time and upon disease progression in patient‐matched biopsies taken at different timepoints. In addition, TF expression in patient‐matched primary tumor and metastatic lesions was also analyzed. Methods and Results: TF expression was detected via immunohistochemistry (IHC) using a validated TF‐specific antibody. TF was expressed in all cancer types tested, with highest prevalence in pancreatic cancer, cervical cancer, colon cancer, glioblastoma, HNSCC, and NSCLC, and lowest in breast cancer. Staining was predominantly membranous in pancreatic, cervical, and HNSCC, and cytoplasmic in glioblastoma and bladder cancer. In general, expression was consistent between biopsies obtained from the same patient over time, although variability was observed for individual patients. NSCLC biopsies of primary tumor and matched lymph node metastases showed no clear difference in TF expression overall, although individual patient changes were observed. Conclusion: This study shows that TF is expressed across a broad range of solid cancer types, and expression is present upon tumor dissemination and over the course of treatment.